Topology and Geometry - Bredon, Glen E. (New York: Springer, 1993)
This book is intended as a textbook for a first-year graduate course on algebraic topology, with as strong flavoring in smooth manifold theory. Starting with general topology, it discusses differentiable manifolds, cohomology, products and duality, the fundamental group, homology theory, and homotopy theory.
Appendices 519-540p.; Bibliography 541-543p.; Index 545-557p.; Reprint 2005
Keywords: Cohomology; Fundamental group; Homology theory; Differentiable manifolds